Alternative mRNA is favored by the A3 haplotype of the EPCR gene PROCR and generates a novel soluble form of EPCR in plasma - Saposnik, Beatrice (American Society of Hematology, 2008)
The endothelial cell protein C receptor also exists in soluble form in plasma (sEPCR), resulting from ADAM17 cleavage. Elevated sEPCR levels are observed in subjects carrying the A3 haplotype, which is characterized by a Ser219Gly substitution in the transmembrane domain, rendering the receptor more sensitive to cleavage. Because sEPCR production is not completely blocked by metalloprotease inhibition, we looked for another mechanism. Comparing mRNA expression patterns and levels in A3 and non-A3 cells from 32 human umbilical cord veins, we detected a truncated mRNA in addition to the full-length mRNA. This truncated mRNA was 16 times more abundant in A3 human umbilical vein endothelial cells than in non-A3 human umbilical vein endothelial cells and encoded a protein lacking the transmembrane domain. We stably expressed a recombinant form of this protein (rEPCRisoform) and a protein mimicking the plasma sEPCR (rEPCRsol). Functional studies of the purified recombinant proteins revealed that the rEPCRisoform bound to recombinant protein C with similar affinity than rEPCRsol and that it also inhibited the anticoagulant activity of APC. Trace amounts of the EPCR isoform were found in the plasma of A3 subjects. These results suggest that the sEPCRisoform could contribute to the regulatory effect of sEPCR in plasma.